Discussion on Computer Information Technology and Network Security Management - Li, Xinyang (Journal of Theory and Practice of Engineering Science, 2025)
In recent years, with the rapid development of China's economy and society and the widespread use of information technology, information technology has become an important means in the development of contemporary society. During the process of social transformation, the application of computer information technology and network security management has achieved significant results. Therefore, network security management is closely related to the development of computer information technology. It stores a large amount of sensitive and important information, and any leakage of information at any level can directly lead to major risk incidents. This highlights the importance of information security management. Based on this, the paper analyzes the relationship between computer information technology and network security management, and the importance of security management work. To further enhance the security of computer information technology applications, the advantages and roles of information technology should be fully utilized to support the network society and comprehensively promote the healthy development of society.